2022
DOI: 10.1007/s00234-022-02957-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cranial nerves in Lyme neuroborreliosis: incidence and correlation with clinical symptoms and prognosis

Abstract: Purpose Symptoms of cranial neuritis are a common presentation of Lyme neuroborreliosis (LNB). Imaging studies are scarce and report contradictory low prevalence of enhancement compared to clinical studies of cranial neuropathy. We hypothesized that MRI enhancement of cranial nerves in LNB is underreported, and aimed to assess the prevalence and clinical impact of cranial nerve enhancement in early LNB. Methods In this prospective, longitudinal cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is interesting in the light of a recent MRI-study of patients with LNB, performed by Lindland et al . [ 32 ]. They found that 51% (19/37) of the patients with MRI signs of facial nerve inflammation and 94% (16/17) of the patients with MRI signs of oculomotor/abducens nerve inflammation did not have clinical signs of corresponding cranial nerve palsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is interesting in the light of a recent MRI-study of patients with LNB, performed by Lindland et al . [ 32 ]. They found that 51% (19/37) of the patients with MRI signs of facial nerve inflammation and 94% (16/17) of the patients with MRI signs of oculomotor/abducens nerve inflammation did not have clinical signs of corresponding cranial nerve palsies.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 51% (19/37) of the patients with MRI signs of facial nerve inflammation and 94% (16/17) of the patients with MRI signs of oculomotor/abducens nerve inflammation did not have clinical signs of corresponding cranial nerve palsies. They conclude that subclinical cranial neuritis is to be expected in a substantial share of patients [ 32 ]. Eventually, the presence of subclinical cranial neuritis without corresponding symptoms can explain why we did not observe associations between sNfL levels and affection of cranial nerves.…”
Section: Discussionmentioning
confidence: 99%
“…7 Imaging findings supportive of LNB include meningeal, leptomeningeal, or neural enhancement though prevalence of these findings varies. [11][12][13] A prospective cohort study of 368 Danish patients with LNB showed only 12%-14% of MRIs demonstrated findings of LNB, 12 but another prospective cohort study of 69 European LNB patients found 57% had cranial nerve enhancement. 13 Patients with longer duration of symptoms are more likely to have LNB findings on MRI, as in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] A prospective cohort study of 368 Danish patients with LNB showed only 12%-14% of MRIs demonstrated findings of LNB, 12 but another prospective cohort study of 69 European LNB patients found 57% had cranial nerve enhancement. 13 Patients with longer duration of symptoms are more likely to have LNB findings on MRI, as in our cases. 12 However, there is frequently lack of correlation between enhancement of cranial nerves or nerve roots and neurologic symptoms, which was also seen in our three cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some find reduced cognitive function, especially in verbal learning and memory [10][11][12], and processing speed [12,13], while others find no differences between patients and healthy controls [14,15]. Apart from leptomeningeal and cranial nerve enhancement in the acute phase, pathological findings on conventional MRI after treated neuroborreliosis are unusual [16][17][18]. MRI with high resolution and advanced image processing which allow quantification of cortical thickness and volume of brain regions has not been applied in patients with neuroborreliosis.…”
Section: Introductionmentioning
confidence: 99%